Lifetime Alcohol Intake, Binge Drinking Behaviors, and Breast Cancer Risk - White, Alexandra J. (Am J Epidemiol, 2017)
The prevalence of binge drinking in the United States is rising. While alcohol is a risk factor for breast cancer, less is known about the impact of episodic heavy drinking. In 2003–2009, women aged 35–74 years who were free of breast cancer were enrolled in the Sister Study (n = 50,884). Residents of the United States or Puerto Rico who had a sister with breast cancer were eligible. Multivariable Cox regression was used to estimate adjusted hazard ratios and 95% confidence intervals for breast cancer. During follow-up (mean = 6.4 years), 1,843 invasive breast cancers were diagnosed. Increased breast cancer risk was observed for higher lifetime alcohol intake (for ≥230 drinks/year vs. <60 drinks/year, hazard ratio (HR) = 1.35, 95% confidence interval (CI): 1.15, 1.58). Relative to low-level drinkers (<60 drinks/year), hazard ratios were increased for ever binge drinking (HR = 1.29, 95% CI: 1.15, 1.45) or blacking out (HR = 1.39, 95% CI: 1.17, 1.64). Compared with low-level drinkers who never binged, moderate drinkers (60–229 drinks/year) who binged had a higher risk (HR = 1.25, 95% CI: 1.08, 1.44). There was evidence of effect modification between moderate lifetime drinking and binging (relative excess risk due to interaction = 0.33, 95% CI: 0.10, 0.57). Our findings support the established association between lifetime alcohol intake and breast cancer and provide evidence for an increased risk associated with heavy episodic drinking, especially among moderate lifetime drinkers.